Cacao butter as prophylaxis for nipple problems: A pilot randomized controlled study - CAN GÜRKAN, ÖZLEM (My University, 2022)
Objective: Cacao butter is a type of oil extracted from the fruit of the Theobroma Cacao plant. This study was conducted to compare the use of breast milk and cacao butter for the prevention of nipple problems in the early postpartum period.Materials and Methods: This randomized controlled study involved 72 participants, who were randomized into the cacao and mother\"s milk groups. Data were collected using Descriptive questionnaire, Nipple assessment form, and IMDAT (Amount of Urine Output, Condition of Breasts, Amount of Stool, Weight Increase and Satisfaction Status).Results: On postpartum day 10, the rates of nipple pain (11.40% cacao group versus 40.50% mother\"s milk group), rashes (14.30% cacao group versus 35.10% mother\"s milk group), and cracks (14.30% cacao group versus 43.20% mother\"s milk group) significantly reduced in the cacao group when compared with the mother\"s milk group (p < 0.05).Conclusion: The application of cacao butter to the nipples is possibly a more effective method than the application of mother\"s milk for preventing nipple pain, rashes, or cracked nipples. Cacao butter can be used prophylactically to prevent nipple problems in the early postpartum period.
Keywords: Tıp; Dahili Tıp Bilimleri; Çocuk Sağlığı ve Hastalıkları; Cerrahi Tıp Bilimleri; Kadın Hastalıkları ve Doğum; Sağlık Bilimleri; Medicine; Internal Medicine Sciences; Child Health and Diseases; Surgery Medicine Sciences; Obstetrics and Gynecology; Health Sciences; KADIN HASTALIKLARI & DOĞUM; Klinik Tıp; Klinik Tıp (MED); PEDİATRİ; OBSTETRICS & GYNECOLOGY; CLINICAL MEDICINE; Clinical Medicine (MED); PEDIATRICS; Pediatri; Pediatri, Perinatoloji ve Çocuk Sağlığı; Doğum ve Jinekoloji; Pediatrics; Pediatrics, Perinatology and Child Health; breastfeeding; nipple problems; nipple cracks; postpartum period; cacao butter; BREAST-MILK; PREVENTION; LANOLIN; PEPPERMINT; DISCHARGE; FISSURE; PAIN; OIL